China's Financial Interlinkages and Implications For Inter-Agency Coordination - Liao, Min (IMF Working Papers; Working Paper, 2016)
China's financial system has become very large, diversified, and interconnected. This changing financial landscape could potentially produce systemic risks, arising primarily from growing financial interconnectedness. The paper argues that, to address the potential systemic risks, Chinese authorities should further strengthen internal coordination, notably by institutionalizing better information collection and sharing among regulators, as well as enhancing coordinated and comprehensive analysis of systemic risk.